A Structural/Functional Domain on Human CD36 Is Involved in the Binding of Anti-Nakα Antibodies - Daviet, Laurent; Morel-Kopp, Marie-Christine; Kaplan, Cécile; McGregor, John L (Thrombosis and Haemostasis, 1995)
The human CD36 antigen is an integral membrane glycoprotein expressed by platelets, monocytes, endothelial cells and various tumor cell lines. CD36 acts as a receptor for thrombospondin, collagen, Plasmodium falciparum-infected erythrocytes and oxidized low- density lipoprotein. Individuals possessing the Naka-negative phenotype do not express CD36 and risk developing anti-CD36 isoantibodies upon blood transfusion or during pregnancy. In the present study, we have examined the interaction of an anti-Naka serum with recombinantly expressed CD36. Results obtained show that five functional CD36 monoclonal antibodies (OKM5, FA6-152, L103, ESIV-C7 and 10/5) prevent the binding of the anti-Naka serum whereas a single monoclonal antibody (13/10) has no effect. Consistent with this result, an epitope map of CD36 generated using cross-blocking experiments, indicates that the inhibitory monoclonal antibodies recognize closely- related epitopes whereas 13/10 reacts with a distinct CD36 determinant. Furthermore, we have demonstrated, in a recent study, that OKM5, FA6-152, L103 and 10/5 bind to the same CD36 domain defined by amino acids 155 to 183. Taken together, our results indicate that the 155-183 sequence is important for the binding of the anti-Naka serum to CD36 and may represent a surface-exposed, immunogenic and presumably functional region on human CD36.